OP11 Do health checks for adults with intellectual disability reduce emergency hospital admissions? Evaluation of a natural experiment. (13th September 2016) - Hosking, FJ; Harris, T; DeWilde, S; Beighton, C; Shah, SM; Cook, DG; Carey, IM
Abstract : Background: Annual health checks for adults with intellectual disability (ID) have been incentivised by NHS England since 2009, but it is unclear what impact they have had on important health outcomes such as emergency hospitalisation. With only half of eligible adults receiving health checks, this provided the opportunity to evaluate the scheme by viewing it as a "natural experiment". Methods: An evaluation, incorporating practice and individual level designs, to assess the effectiveness of health checks for adults with ID in reducing emergency hospital admissions using a large English primary care database. For the practice analysis, change in admission rates for all adults with ID between 2009–10 and 2011–12 were compared in 126 fully participating (≥50% of ID adults with a health check) versus 68 non-participating practices (<25% with health check). For the individual analysis, changes in admission rates from before to after first health check for 7, 487 adults with ID were compared to 46, 408 age-sex-practice matched controls without ID. Incident rate ratios (IRR) comparing change in admission rates are presented for: all emergency admissions, preventable emergency admissions (for Ambulatory Care Sensitive (ACS) conditions) and elective admissions. Results: Practices with high health check participation showed no change in emergency admission rate among patients with ID over time compared to non-participating practices (IRR = 0.97, 95% CI 0.78–1.19), but emergency admissions for ACS conditions did fall (IRR = 0.73, 95% CI 0.57–0.95). Among individuals with ID, health checks had no effect on overall emergency admissions compared to population controls (IRR = 0.96, 95% CI 0.87–1.07), although a trend towards a reduction in emergency admissions for ACS conditions was noted (IRR = 0.83, 95% CI 0.68–1.01). ID patients with high levels of support needs showed a fall in overall emergency admission rate post health check compared to controls (IRR = 0.80, 0.67–0.95). Elective admissions showed no change with health checks in either analysis. Conclusion: Annual health checks in primary care for adults with ID did not alter overall emergency admissions, but they appeared influential in reducing preventable emergency admissions, as well as emergency admissions for those with more complex health needs. Increasing the uptake of health checks for adults with ID, particularly those with more complex health needs, would reduce inequalities and improve health care in this disadvantaged group.